2009
DOI: 10.1016/j.jbi.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Tracking medical students’ clinical experiences using natural language processing

Abstract: Graduate medical students must demonstrate competency in clinical skills. Current tracking methods rely either on manual efforts or on simple electronic entry to record clinical experience. We evaluated automated methods to locate 10 institution-defined core clinical problems from three medical students’ clinical notes (n = 290). Each note was processed with section header identification algorithms and the KnowledgeMap concept identifier to locate Unified Medical Language System (UMLS) concepts. The best perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…Recently, natural language processing-based (NLP) approaches have come into use, with the goal of improving information retrieval by using computer algorithms to analyse and process the information found in clinical texts (especially in unstructured texts) [14].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Recently, natural language processing-based (NLP) approaches have come into use, with the goal of improving information retrieval by using computer algorithms to analyse and process the information found in clinical texts (especially in unstructured texts) [14].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We have previously shown that we could develop algorithms to identify broad topics of interest in students' clinical notes (e.g. ''chest pain'', ''fever'' -each of which involve other related concepts encompassing associated symptoms, evaluations and treatments) (Denny et al 2009). This functionality allows students to search their clinical notes in VLP for these specific topics; the system scores each note with a numerical relevance score based on the algorithm provided.…”
Section: Introductionmentioning
confidence: 99%
“…Medical schools using 108 competency-based assessments typically rely on education portfo-109 lios to track each student's progress [10][11][12][13][14]. Portfolio components Handwritten log books [15,16] or electronic logs [17,18] allow stu-115 dents to record patient information including demographics, diag-116 nosis, procedures performed, and/or severity of illness.…”
mentioning
confidence: 99%
“…Capture 117 rates of learners' experiences are low because trainees are too busy 118 to enter the data into the system [15,19]. Further, teachers often 119 disagree with students on the primary diagnosis of the case 120 [16,20] [14,26]. In use since 2005, Portfolio currently includes 142 nearly 5 million indexed trainee-authored notes.…”
mentioning
confidence: 99%
See 1 more Smart Citation